Recent advances in radiobiology with respect to pleiotropic aspects of tissue reaction. (5th May 2021) - Suzuki, Keiji; Amrenova, Aidana; Mitsutake, Norisato
ABSTRACT: DNA double-strand breaks (DSBs) induced by ionizing radiation are the major cause of cell death, leading to tissue/organ injuries, which is a fundamental mechanism underlying the development of tissue reaction. Since unscheduled senescence, predominantly induced among epithelial tissues/organs, is one of the major modes of cell death in response to radiation exposure, its role in tissue reaction has been extensively studied, and it has become clear that senescence-mediated secretion of soluble factors is an indispensable component of the manifestation of tissue reaction. Recently, an unexpected link between cytoplasmic DSBs and innate immunity was discovered. The activation of cyclic GMP-AMP (cGAMP) synthase (cGAS) results in the stimulation of the cGAS–stimulator of interferon genes (STING) pathway, which has been shown to regulate the transactivation of a variety of secretory factors that are the same as those secreted from senescent cells. Furthermore, it has been proven that cGAS–STING pathway also mediates execution of the senescence process by itself. Hence, an autocrine/paracrine feedback loop has been discussed in previous literature in relation to its effect on the tissue microenvironment. As the tissue microenvironment plays a crucial role in cancer development, tissue reaction could be involved in the late health effects caused by radiation exposure. In this paper, the novel findings in radiation biology, which should provide a better understanding of the mechanisms underlying radiation-induced carcinogenesis, are overviewed.